The Impact of Job Stress on Job Satisfaction and Adaptive Performance Moderated by Social Support: Study at Bank Jatim Kediri Branch Regional Office - Dewi Nurfadhillah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The purpose of this is to analyze the effect of job stress on job satisfaction and adaptive performance with social support as a moderating variable. This research is causality research with a quantitative approach. This research is a causality study with a quantitative approach. Determination of the sample using probability sampling with proportionate stratified random sampling technique with a total of 86 respondents at Bank Jatim Kediri Branch Regional Office. The statistical analysis used in this research is SEM PLS with the help of WarpPLS 8.0 software. The result of the analysis obtained from this study indicates that job stress has a negative and significant effect on job satisfaction; job stress has a negative and significant on adaptive performance; social support can moderate significantly the effect of job stress on job satisfaction and adaptive performance.